Comet C/2012 S1 (ISON) coma composition at 4 au from HST observations. (1st December 2015) - Zubko, Evgenij; Videen, Gorden; Hines, Dean C.; Shkuratov, Yuriy; Kaydash, Vadym; Muinonen, Karri; Knight, Matthew M.; Sitko, Michael L.; Lisse, Carey M.; Mutchler, Max; Wooden, Diane H.; Li, Jian-Yang; et al.
Abstract: We analyze the first color and polarization images of Comet ISON (C/2012 S1) taken during two measurement campaigns of the Hubble Space Telescope (HST) on UTC 2013 April 10 and May 8, when the phase angles of Comet ISON were α ≈13.7° and 12.2°, respectively. We model the particles in the coma using highly irregular agglomerated debris particles. Even though the observations were made over a small range of phase angle, the data still place significant constraints on the material properties of the cometary coma. The different photo-polarimetric responses are indicative of spatial chemical heterogeneity of coma in Comet ISON. For instance, at small projected distances to the nucleus (<500 km), our modeling suggests the cometary particles are composed predominantly of small, highly absorbing particles, such as amorphous carbon and/or organics material heavily irradiated with UV radiation; whereas, at longer projected distances (>1000 km), the refractive index of the particles is consistent with organic matter slightly processed with UV radiation, tholins, Mg−Fe silicates, and/or Mg-rich silicates contaminated with 10% (by volume) amorphous carbon. The modeling suggests low relative abundances of particles with low material absorption in the visible, i.e., Im( m )≤0.02. Such particles were detected unambiguously in other comets in the vicinity of nucleus through very strong negative polarization near backscattering ( P ≈−6%) and very low positive polarization ( P ≈3–5%) at side scattering. These materials were previously attributed to Mg-rich silicates forming a refractory surface layer on the surface of cometary nuclei (Zubko et al., 2012 ). The absence of such particles in Comet ISON could imply an absence of such a layer on its nucleus. Highlights: We model the photopolarimetric response of Comet ISON measured at rh 4 au. Different photopolarimetric responses are indicative of spatial chemical heterogeneity. We can place constraints on the types of particles in each region. The innermost coma where a jet is detected contains small, highly absorbing particles. The outer coma can be modeled with different types of particles.